Standards Application in Very Small Enterprises. - Laporte, Claude Y. (Computer (00189162), 2007)
The article discusses efforts of the WG24 working group to devise software engineering standards for very small enterprises (VSEs). A survey of VSEs from 32 countries revealed several factors that prevented the use of standards, including lack of resources, no requirement from customers to adhere to them, and the overly bureaucratic nature of complying with existing standards. WG24 will combine elements of International Organization for Standardization (ISO) strictures with those from specific countries to come up with a regime suitable for VSEs.